أثر تقديم القياس وتأخيره بين الأدلة في الأصول والفروع = The effect of prioritization of analogy (Qiyas) among the evidences on principles of Islamic Jurisprudence and its branches - Mat Jubri@Shamsuddin, Mustafa (Sultan Sharif Ali Islamic University Brunei, 2020)
Analogy (Qiyas) has been considered as the fourth juristic evidence after al-Quran, al-Sunnah and al-Ijma’ in the process of reasoning among scholars. This indicates that the Analogy is principally ranked after these three evidences and never surpass them. But those who are studying the scholars’ writings find the contrary, as the analogy might be prioritized upon the other evidences for certain reasons and factors. Hence, this research attempts to study the rank of analogy among the juristic evidences by emphasizing on the different opinions of scholars and their arguments, and the effect of this rank on some issues in principles of Islamic Jurisprudence and its branches. This research follows firstly inductive method in gathering the related data to this topic, and secondly analytical method in scrutinizing the data in order to come out with the solutions and suggestions.